Viajeros rumanos en España, en busca de las raíces comunes - Anghelescu, Mircea (Revista de Filología Románica, 2006)
Flashed by The Alhambra Tales of Washington Irving, the Romanian writer Mihail Koga˘lniceanu made, in 1846, a travel to Spain which allowed him to see the parallelism between our country and the Balcanic one. He opened the way to traveller writers such as Nicolae Iorga (1927) or Mihai Tican (1929), which explored in the relationships between the two countries.